Role of horizontally transferred copper resistance genes in Staphylococcus aureus and Listeria monocytogenes. Issue 4 (11th April 2022) - Kaur, Inderpreet; Purves, Joanne; Harwood, Matthew; Ketley, Julian M.; Andrew, Peter W.; Waldron, Kevin J.; Morrissey, Julie A.
Abstract : Bacteria have evolved mechanisms which enable them to control intracellular concentrations of metals. In the case of transition metals, such as copper, iron and zinc, bacteria must ensure enough is available as a cofactor for enzymes whilst at the same time preventing the accumulation of excess concentrations, which can be toxic. Interestingly, metal homeostasis and resistance systems have been found to play important roles in virulence. This review will discuss the copper homeostasis and resistance systems in Staphylococcus aureus and Listeria monocytogenes and the implications that acquisition of additional copper resistance genes may have in these pathogens.